The Role of Habit and Emotional Regulation on Entertainment Video - Ozkaya, Elif (Journal of New Media and Mass Communication, 2016)
Communication research has largely sought to explore how users come to consume media. This study examines audience selection of entertainment media, in particular television program genres streamed in the online environment. By drawing from social cognitive theory, it is the aim of this study to investigate whether acts of emotional self-regulation can provide an explanation for selective exposure to media entertainment. In an experimental setting, mood management theory and social cognitive theory are pitted against each other in determining content preference under the influence of sad moods. Putting all subjects in a sad mood, and manipulating habit strengths for comedic and dramatic content, it is predicted that subjects whose emotional self-regulation is depleted will select more habitual entertainment video options than non-depleted subjects.